Myeloid cell deficiency of p38γ/p38δ protects against candidiasis and regulates antifungal immunity - Alsina‐Beauchamp, Dayanira; Escós, Alejandra; Fajardo, Pilar; González‐Romero, Diego; Díaz‐Mora, Ester; Risco, Ana; Martín‐Serrano, Miguel A; del Fresno, Carlos; Dominguez‐Andrés, Jorge; Aparicio, Noelia; Zur, Rafal; Shpiro, Natalia; et al. (EMBO molecular medicine, 2018)
Candida albicans is a frequent aetiologic agent of sepsis associated with high mortality in immunocompromised patients. Developing new antifungal therapies is a medical need due to the low efficiency and resistance to current antifungal drugs. Here, we show that p38γ and p38δ regulate the innate immune response to C. albicans . We describe a new TAK1‐TPL2‐MKK1‐ERK1/2 pathway in macrophages, which is activated by Dectin‐1 engagement and positively regulated by p38γ/p38δ. In mice, p38γ/p38δ deficiency protects against C. albicans infection by increasing ROS and iNOS production and thus the antifungal capacity of neutrophils and macrophages, and by decreasing the hyper‐inflammation that leads to severe host damage. Leucocyte recruitment to infected kidneys and production of inflammatory mediators are decreased in p38γ/δ‐null mice, reducing septic shock. p38γ/p38δ in myeloid cells are critical for this effect. Moreover, pharmacological inhibition of p38γ/p38δ in mice reduces fungal burden, revealing that these p38MAPKs may be therapeutic targets for treating C. albicans infection in humans. Synopsis Candida albicans infections cause high mortality in immunocompromised patients. This study shows that p38γ/p38δ are essential for the immune response to C. albicans by regulating host antifungal activity. p38γ/p38δ inhibition reduces mice fungal burden, establishing p38γ/p38δ as therapeutic targets. Deletion of p38γ/p38δ protects mice from C. albicans infection. p38γ/p38δ control fungicidal capacity through ROS and iNOS production. p38γ/p38δ regulate the inflammatory response to C. albicans through a new Dectin‐1 pathway in macrophages. Chemical inhibition of p38γ/p38δ reduces fungal burden in a candidiasis mouse model. Graphical Abstract Candida albicans infections cause high mortality in immunocompromised patients. This study shows that p38γ/p38δ are essential for the immune response to C. albicans by regulating host antifungal activity. p38γ/p38δ inhibition reduces mice fungal burden, establishing p38γ/p38δ as therapeutic targets.